2020
DOI: 10.1093/nop/npaa064
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of the impact of radiotherapy and chemotherapy in elderly patients with glioblastoma based on age and performance status

Abstract: Background This retrospective study investigated the impact of Karnofsky performance status (KPS), in addition to age, on the management and outcomes of elderly patients with glioblastoma (GBM). Methods The National Cancer Database was queried between 2004–2015 for GBM patients with age ≥60. Three age groups were created: 60-69, 70-79, and ≥ 80 years old, and four age/KPS groups: ‘Age≥ 60/ KPS<70’ (group 1), ‘Age 60-69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The WHO performance status was most strongly correlated while age was not independently correlated with the OS in our study. This is in accordance with the results of a recent retrospective study of Al Feghali et al 14 Their study is based on the National Cancer Database Query between 2004 and 2015 of GBM patients with median age of 70 years at diagnosis. In the study the median OS was 10.45 months, 5.78 months, and 3.52 months in age groups 60–69 years, 70–79 years, and >80 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The WHO performance status was most strongly correlated while age was not independently correlated with the OS in our study. This is in accordance with the results of a recent retrospective study of Al Feghali et al 14 Their study is based on the National Cancer Database Query between 2004 and 2015 of GBM patients with median age of 70 years at diagnosis. In the study the median OS was 10.45 months, 5.78 months, and 3.52 months in age groups 60–69 years, 70–79 years, and >80 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Performance status is a key prognostic factor to be considered for management decisions in elderly patients with newly diagnosed glioblastoma ( 69 ). Retrospective studies identified predictors for poor OS of older age, lower KPS, white people, higher comorbidity score, worse socioeconomic status, community treatment, tumor multifocality, STR, aphasia after surgery, motor dysfunction after surgery and no adjuvant treatment ( 30 , 69–74 ).…”
Section: Prognostic Markersmentioning
confidence: 99%
“…The National Cancer Database (NCDB) is a joint project of the Commission on Cancer (CoC) of the American College of Surgeons (ACoS) and the American Cancer Society. The NCDB collects data from more than 1,500 hospitals with ACoS-accredited cancer programs, accounting for 70% of all newly diagnosed cancers cases in the United States [ 15 - 17 ]. It includes data on tumor characteristics, patient demographics, and survival.…”
Section: Methodsmentioning
confidence: 99%